2005
DOI: 10.4049/jimmunol.175.8.5439
|View full text |Cite
|
Sign up to set email alerts
|

Nonpathogenic, Environmental Fungi Induce Activation and Degranulation of Human Eosinophils

Abstract: Eosinophils and their products are probably important in the pathophysiology of allergic diseases, such as bronchial asthma, and in host immunity to certain organisms. An association between environmental fungal exposure and asthma has been long recognized clinically. Although products of microorganisms (e.g., lipopolysaccharides) directly activate certain inflammatory cells (e.g., macrophages), the mechanism(s) that triggers eosinophil degranulation is unknown. In this study we investigated whether human eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(131 citation statements)
references
References 58 publications
4
126
1
Order By: Relevance
“…71 In addition, antiviral effects have been reported. 72 Investigations of the role of eosinophils in fungal infection with Candida albicans, [73][74][75] Alternaria alternata, 76 or C. neoformans 10,23,41,42 were made, with a focus on their effector function. Similarly, a study 10 using anti-IL-5 treatment showed an association of eosinophil frequency with susceptibility during cryptococcosis.…”
Section: Discussionmentioning
confidence: 99%
“…71 In addition, antiviral effects have been reported. 72 Investigations of the role of eosinophils in fungal infection with Candida albicans, [73][74][75] Alternaria alternata, 76 or C. neoformans 10,23,41,42 were made, with a focus on their effector function. Similarly, a study 10 using anti-IL-5 treatment showed an association of eosinophil frequency with susceptibility during cryptococcosis.…”
Section: Discussionmentioning
confidence: 99%
“…The virulence factors in these fungi that are responsible for eliciting allergic reactions are not well understood, though Alternaria was found to stimulate the degranulation of eosinophils, possibly due to an aspartic protease (372,496). These organisms are very common in the environment, so exposure is practically universal, though the incidence of allergic disease is relatively low, suggesting that host factors may play a role.…”
Section: Other Putative Virulence Factorsmentioning
confidence: 99%
“…In this regard, a recent report analyzing Siglec-F null mice revealed enhanced eosinophil infiltration and blood eosinophilia in response to allergen challenge, suggesting that Siglec-F is a negative regulator of eosinophil response to allergens (86). Eosinophils also contribute to an immune response against foreign pathogens, including binding, engulfment, and killing of microbes (1,15,19,32,36,83). While investigating the endocytic activity of Siglec-F, we observed efficient endocytosis of anti-Siglec antibody, high-affinity sialoside ligand probes, and Neisseria meningitidis bearing sialylated glycans.…”
mentioning
confidence: 99%